Acceptable range of timing error at bat-ball impact in baseball depends on the bat swing path - Nakashima, Hirotaka; Horiuchi, Gen; Kimura, Arata; Sakurai, Shinji (Frontiers in Sports and Active Living, 2025)
IntroductionIn baseball, a common instruction emphasizes aligning the bat swing trajectory with the pitched ball trajectory near impact when viewed from the side. This alignment is believed to widen the acceptable range of timing error, thereby enhancing batting average. While prior studies have explored the effects of swing speed and sweet spot contact on batted ball velocity, the specific influence of bat swing path on the acceptable range of timing error during bat-ball impact has not been adequately investigated. We aimed to quantify the acceptable range of timing error and to investigate the swing characteristics that influence this range.MethodsEighteen pitched ball trajectories thrown by 10 collegiate pitchers and 145 bat swing trajectories performed by 29 collegiate batters were acquired in independent experimental settings. From these trajectories, the acceptable time and distance ranges of timing error, in which the ball could be impacted by the bat's sweet spot, were calculated.Result and discussionThe average acceptable range of timing error was 9.36 ± 6.25 ms in time and 0.227 ± 0.163 m in distance. However, these ranges varied significantly (time: 2.48–30.40 ms; distance: 0.056–0.614 m) depending on the specific swing trajectory. Furthermore, our findings revealed that the acceptable range of timing error is not solely determined by a single swing characteristic but rather by the interplay of multiple factors, including the bat swing trajectory as viewed from the side and above and the bat angle at impact. These results suggest a need for a multifaceted approach to swing instruction, considering these inter-related factors to optimize a batter's ability consistently to make solid contact.